ARAHAN KOMODITAS UNGGULAN PERIKANAN TAMBAK DI PESISIR KABUPATEN KENDAL (EVALUASI KESESUAIAN LAHAN BUDIDAYA PERIKANAN TAMBAK) - Sriyanto, Sriyanto; Sanjoto, Tjaturahono Budi (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2017)
Many factors are taken into consideration when it will breed pond fishery. Location clearance, soil ph, soil texture, land slope, distance to sea, distance to river, rainfall, and axisibility are some of the necessary equilibrium. The right conditions with these parameters will provide maximum results for fish farmers, otherwise if these parameters are not met it will affect the results that will be obtained. Kendal Regency is one of the regencies in Central Java with coastal area. There are 7 districts in Kendal Regency whose territory is on the coast, Kaliwungu, Patebon, Brangsong, Rowosari, Kangkung, Kendal, and Cepiring. The purpose of this study is to assess the suitability class of ponds in coastal areas of Kendal. The method used is the scoring analysis of the parameters of the location of a good pond, among others, land slope, soil texture, soil ph. Based on the parameters used in the evaluation of land suitability, in the coastal region of Kendal Regency can be classified into three classes, namely very appropriate (S1) covering the District Kangkung and District Rowosari. The corresponding class (S2), the region's distribution in this class is almost in most coastal areas of Kendal Regency. In the quite appropriate class (S3) is the class of land that if it will be cultivated ponds need special treatment is located in Kendal and Kaliwungu District because most of the land for settlement and moor. To achieve the target of pond production, it needs to be cultivated in a very suitable class (S1). This is considering almost no obstacles in cultivating ponds.